The Influence of Mild Pulsed Electric Field (PEF) on Acid Tolerance, Bile Tolerance, Growth and Protease Activity of the Dairy Culture Bacteria Lactobacillus acidophilus LA-K - Najim, Najim H. (The Iraqi Journal of Veterinary Medicine, 2013)
The objective of this study was to determine the influence of mild PEF conditions on acid tolerance, growth, bile tolerance and protease activity of L. acidophilus LA-K. The treatments were positive square unipolar pulse width of 3 µs, pulse period of 0.5 second, voltage of 1 kV/cm, delay time of 20 µs and flow rate of 60 ml/min at 40.5°C PEF treatment temperature. The control was passed through the PEF system at the same flow rate (60 ml/min) without receiving any pulsed electric field condition. The acid tolerance was determined every 30 minutes for 120 minutes of incubation in acidified MRS broth at pH 2. Growth of the culture was determined hourly for 32 hours of incubation at 37°C in MRS broth. The bile tolerance was determined hourly for 16 hours of incubation in MRS-Thio broth supplemented with 0.3% (w/v) Oxgall (bovine bile) and 0.2% sodium thioglycolate. Samples were plated in duplicates using Lactobacilli MRS agar. The petriplates were incubated anaerobically at 37C for 48 hours. Protease activity was determined by o-phthaldialdehyde (OPA) spectrophotometric assay at 0, 12, 24, 36 and 48 hours of incubation of inoculated skim milk at 40°C three replications were conducted. The experimental design was repeated measurements on complete randomized block, replications were the blocks. Lactobacillus acidophilus subjected to mild PEF conditions as well as the control were acid tolerant until the end of the 120 minutes of incubation but there was a significant (P<0.0001) decrease in the viable bacterial counts after each incubation time of 30 minutes. Mild PEF conditions studied significantly improved acid tolerance of the bacterium. The mild PEF treated culture reached the logarithmic phase of the growth an hour earlier than the control. Lactobacillus acidophilus LA-K exhibited tolerance to the bile conditions and exhibited similar growth patterns in the presence or absence of bile acids but the bacterium reached the stationary phase after 12 hours of incubation in bile conditions compared to 16 hours of incubation in the absence of bile conditions. Mild Pulsed Electric Field conditions had insignificant effect on bile tolerance of L. acidophilus LA-K. Mild Pulsed Electric Field treatment significantly (P<0.0001) enhanced the protease activity of the bacterium compared to the control.